Identifying the subgroups of depression trajectories among the middle-aged and older Chinese individuals with chronic diseases: an 8-year follow-up study based on CHARLS - Pei, Jiaxing; Hu, Mei; Lu, Qiang; Zhou, Pengfei; Shang, Yijing; Zhang, Huiwang; Yang, Xiaoguang; Li, Yunming (Frontiers in Public Health, 2024)
Background: Prior studies have demonstrated a prevalent occurrence of depression among the middleaged and elderly Chinese individuals with chronic diseases. Nevertheless, there is limited research on the specific subgroups of depression trajectories within this population and the factors influencing these subgroups.Objective: To explore the changing trajectory and influencing factors of depression in the middle-aged and elderly individuals with chronic disease in China, and provide the data reference for the health management of the elderly population in China.